О задачах эволюционной морфологии - Матвеев, Б.С. (Вестник зоологии, 1969)
Discussing the evolutionary trends of the Modern Synthesis of Evolution according to E. Mayr the return of the modern biology to the study of Ch. Darvin is observed. Two evolutionary trends are distinguished: evolutionary biological progress and studying the evolution of ontogeny. Studying the evolution of ontogeny in phylogenetical development of animals makes it possible to master the control methods of animal development bv a man.